Transformative Justice in Practice: Reflections on the Pastoral Land Commission During Brazil’s Political Transition - Hoddy, Eric Timothy (Journal of Human Rights Practice, 2021)
There has been a growing interest among transitional justice academics and practitioners in pursuing more transformative agendas for practice. There remain however few illustrations, if any, of work to deliver transformative justice in practice. This article considers the work of Brazil’s Pastoral Land Commission (CPT) during Brazil’s political transition as a potentially useful source of insights for practice. An organ of the Catholic Church and ecumenical in orientation, the CPT worked directly with marginalized communities to defend and promote the rights of small farmers and rural workers and peaceful solutions to land and labour conflicts. Its work was steered by a forward-looking vision of justice in which the violence, marginalization and exclusion of the past and present would be overcome by empowering rural populations to transform their social circumstances and address root causes. This article outlines the practices and activities through which the CPT sought to foster transformative change and reflects on what lessons these might hold for transformative justice in transitional settings.